Cure the Incurable? Recent Breakthroughs in Immune Checkpoint Blockade for Hepatocellular Carcinoma - Pei-Yi Chu (MDPI AG, 2021)
HCC usually arises from a chronic inflammation background, driven by several factors including fatty liver, HBV/HCV viral infection and metabolic syndrome. Systemic treatment for advanced HCC remains disappointing due to its strong resistance to chemotherapy and even to tyrosine kinase inhibitors (TKIs). Recently, the use of ICI therapy has revolutionized the systemic treatment of advanced HCC. For the first time, clinical trials testing ICIs, anti-CTLA-4 and anti-PD1/PDL1 reported a survival benefit in patients with sorafenib resistance. However, it took four more years to find the right combination regimen to use ICI in combination with the anti-angiogenic agent bevacizumab to substantially prolong overall survival (OS) of patients with advanced HCC after sorafenib. This review provides a comprehensive history of ICI therapy in HCC, up-to-date information on the latest ICI clinical trials, and discusses the recent development of novel ICIs that would potentially lead to a new checkpoint blockade therapy for advanced HCC.